Implementasi Pembelajaran Tematik Melalui Media Pembuatan Teh Bunga Rosela (Teburos) untuk Meningkatkan Keterampilan Wirausaha Siswa - Wicaksono, Iwan; Sihrahayu, Reni; Sudarti, Sudarti; Wuryaningrum, Rusdhianti (PGSD Universitas Muria Kudus, 2024)
This research aims to implement thematic learning through the medium of making roselle flower tea (teburos) to improve the entrepreneurial skills of class VI students at SD Negeri Rojopolo 06.The research method used was classroom action research involving 20 students as research subjects. The research steps involve planning, pre-test, implementation, observation, post-test and reflection. The implementation of this learning is a pre-test, providing thematic material, planting roselle plants, active involvement of students in making and packaging Teburos products, developing students' analytical skills in marketing Teburos products, as well as post-tests and reflections. The data collection method used was giving tests to students.From the research results, it is known that the implementation of thematic learning through the teburos media can show improvement. This increase can be seen from the comparison of the average pre-test and post-test scores of students, which experienced a significant increase of 65% from the pre-test score of 55.75, increasing to the post-test of 75.25. The application of thematic learning using Teburos media can improve students' entrepreneurial skills and have a positive impact on students' learning motivation.